Risk assessment study for storage explosive - Saiful Azhar, Saad; Abdul Rahman, M.; Saari, Mustapha; Farizul Hafiz, Kasim; Suhardy, Daud (Science Publications, 2008)
Link to publisher's homepage at http://scipub.org/scipub/index.php